Sales Monitoring Information System at Mojokopi Coffee Shop Using Website-Based Moving Average Method - Renita Oktaviani Irawan; Ucuk Darusalam; Benrahman (Institute of Computer Science (IOCS), 2021)
Mojokopi is a small coffee shop engaged in the sale of various kinds of coffee products such as milk coffee, Toraja coffee, Flores coffee and others. In the coffee sale transaction at Mojokopi, there is a flow where the buyer must first see the list of menus available at the coffee shop, then the seller will record the order into the book according to the buyer's order, if the order is complete, the buyer will pay according to what the buyer ordered. Of course, it really needs a system to be able to simplify the process of transactions so that the data will be faster and safer than the bookkeeping process. The mojokopi coffee shop sales monitoring information system based on the website can process transaction data so as to produce information in monitoring sales reports without having to open documents, as well as using the application of sales forecasting to get sales prediction results. This website-based monitoring information system conducts interviews and direct observations as a method of data collection. It is designed using the PHP and MYSQL programming languages. With the existence of a monitoring information system, existing problems from monitoring sales can be resolved, therefore a website-based information system is designed.